THE INFLUENCE OF READING HABIT AND WRITING MOTIVATION ON WRITING ABILITY OF AL HUDA VOCATIONAL HIGH SCHOOL PEKANBARU - bishry, hasanul (Komunitas Manajemen Kompetitif, 2017)
This research aimed to investigate the influence of reading habit and writing motivation on students’ writing ability of the second-year students of Al Huda Vocational High School Pekanbaru. This research was a survey research and used multiple regression in analyzing the data. The subject of this research was the second-year students of Al Huda Vocational High School Pekanbaru that consisted of three majors: Accounting 26 male students, Secretary 22 female students, and Network Computer 16 students. The total sample was 64 students. The technique of sample collection was census sampling where all the population became the sample of the research. In the data collection, two instruments were used, they were a questionnaire and a test. The questionnaire was used to collect the data of the students’ reading habit and writing motivation, while the test was used to collect the data of the students’ writing ability. The data of this research were analyzed by using Pearson Product Moment and multiple regressions by using SPSS v.20 to get the result of the research. The result of this research indicated that the students’ writing ability was categorized into “high”,, while the students’ writing motivation was categorized into“very well”, and the students’ writing ability was categorized into “weak.” From Pearson Product Moment result and multiple regression, there was an effect of reading habit toward the students’ writing ability, while there was an effect of writing motivation toward the students’ writing ability, and there was a significant influence of reading habit and writing motivation toward the students’ writing ability. Keywords: reading habit, writing motivation, writing ability